Comparing Potassium-Competitive Acid Blocker And Proton Pump Inhibitor For Gastroeshopageal Reflux Disease: A Systematic Review And Meta-Analysis - Ida Bagus Putra Narendra (Riviera Publishing, 2025)
Clinical management is typically used to treat gastroesophageal reflux disease (GERD). Assessed individuals with a range of clinical symptoms of gastroesophageal reflux disease (GERD) to determine the safety and effectiveness of potassium-competitive acid blockers (PCABs). By examining core databases, studies comparing PCABs and proton pump inhibitors (PPIs) in clinical gastroesophageal reflux disease (GERD) and PPI-resistant GERD were identified. In nine randomized controlled trials (RCTs) evaluating the first care of GERD, the risk ratio for healing with PCABs versus PPIs was 1.09 (95% CI, 1.04-1.13) at 2 weeks and 1.03 (95% CI, 1.00-1.07) after 8 weeks, respectively. While 86.3% of PPI-resistant GERD patients reported an improvement in symptom frequency, 90.7% of patients showed improvement in five observational trials. When it comes to the initial and ongoing treatment of GERD, especially severe GERD, PCABs are more effective and have a quicker therapeutic effect than PPIs. However, PCABs might be a different kind of treatment for GERD and GERD that is resistant to PPIs.